Dachaihu decoction ameliorates septic intestinal injury via modulating the gut microbiota and glutathione metabolism as revealed by multi-omics. (10th August 2023) - Huang, Na; Wei, Yu; Liu, Meng; Yang, Zhen; Yuan, Kang; Chen, Jingli; Wu, Zhixin; Zheng, Fanghao; Lei, Kaijun; He, Mingfeng
Abstract: Ethnopharmacological relevance: Dachaihu decoction (DCH), a classic formula for Yangming and Shaoyang Syndrome Complex recorded in "Treatise on Cold Damage", has been widely used in treating intestinal disorders and inflammatory diseases with few side effects in China. However, the mechanism of DCH on septic intestinal injury (SII) remains to be explored. Aim of the study: This study aimed to clarify the mechanism of DCH on SII. Materials and methods: SII model of rat, established by cecal ligation and puncture (CLP), was used to study the effect of DCH on SII. 24 h mortality was recorded. Histological changes were observed by H&E staining. The expression of tight junction protein ZO-1 (ZO-1) and mucin2 (MUC2) was determined by immunohistochemical analysis. Secretory IgA (sIgA), diamine oxidase (DAO) and intestinal fatty acid binding protein (iFABP) were determined by enzyme-linked immunosorbent assay (ELISA). IL-1β, IL-6 and TNF-α were measured by ELISA and quantitative Real-time PCR (RT-qPCR). The gut microbiota was analyzed by 16S rRNA sequencing. The potential targets and pathways of DCH in treating SII were analyzed by integrative analysis of transcriptomic and metabolomic methods. Total glutathione (T-GSH), GSH, GSSG (reduced form of GSH), GSH peroxidase (GPX), superoxide dismutase (SOD), malonaldehyde (MDA) and indicators of hepatic and renal function were measured by biochemical kits. Results: Medium dose of DCH improved 24 h mortality of SII rats, reduced the pathological changes of ileum, and increased the expression levels of ZO-1, MUC2 and sIgA. DCH decreased DAO, iFABP of serum and IL-1β, IL-6, TNF-α of ileum. DCH improved α- and β-diversity and modulated the structure of gut microbiota, with Escherichia_Shigella decreased and Bacteroides and Ruminococcus increased. GSH metabolism was identified as the key pathway of DCH on SII by integrative analysis of transcriptome and metabolome. GSH/GSSG and the most common indicators of oxidative stress, were validated. Antioxidative T-GSH, GSH, GPX and SOD were increased, while MDA, the mark of lipid peroxidation was downregulated by DCH. Eventually, DCH was proved to be safe and hepato- and nephro-protective. Conclusion: DCH ameliorated septic intestinal injury possibly by modulating the gut microbiota and enhancing glutathione metabolism of SII rats, without hepatotoxicity and nephrotoxicity. Graphical abstract: Image 1 Highlights: The intestine is the prior target and "motor" of sepsis. DCH increased ileum ZO-1, muc2, sIgA and decreased inflammatory cytokines of septic intestinal injury (SII) of rats. DCH modulated the gut microbiota of SII rats. The underlying mechanism might be enhanced GSH metabolism as revealed by joint analysis of transcriptomics and metabolomics.